Regulation of Mitochondrial Glutathione Redox Status and Protein Glutathionylation by Respiratory Substrates - Garcia, Jerome (American Society for Biochemistry and Molecular Biology, 2010)
Brain and liver mitochondria isolated by a discontinuous Percoll gradient show an oxidized redox environment, which is reflected by low GSH levels and high GSSG levels and significant glutathionylation of mitochondrial proteins as well as by low NAD(P)H/NAD(P) values. The redox potential of brain mitochondria isolated by a discontinuous Percoll gradient method was calculated to be −171 mV based on GSH and GSSG concentrations. Immunoblotting and LC/MS/MS analysis revealed that succinyl-CoA transferase and ATP synthase (F(1) complex, α-subunit) were extensively glutathionylated; S-glutathionylation of these proteins resulted in a substantial decrease of activity. Supplementation of mitochondria with complex I or complex II respiratory substrates (malate/glutamate or succinate, respectively) increased NADH and NADPH levels, resulting in the restoration of GSH levels through reduction of GSSG and deglutathionylation of mitochondrial proteins. Under these conditions, the redox potential of brain mitochondria was calculated to be −291 mV. Supplementation of mitochondria with respiratory substrates prevented GSSG formation and, consequently, ATP synthase glutathionylation in response to H(2)O(2) challenges. ATP synthase appears to be the major mitochondrial protein that becomes glutathionylated under oxidative stress conditions. Glutathionylation of mitochondrial proteins is a major consequence of oxidative stress, and respiratory substrates are key regulators of mitochondrial redox status (as reflected by thiol/disulfide exchange) by maintaining mitochondrial NADPH levels.